Design of Solar PV Cell Based Inverter for Unbalanced and Distorted Industrial Loads - Naga Ananth D; Venkata Nagesh Kumar (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
PV cell is getting importance in low and medium power generation due to easy installation, low maintenance and subsidies in price from respective nation. Most of the loads in distribution system are unbalanced and distorted, due to which there will be unbalanced voltage and current occur at load and may disturb its overall performance. Due to these loads voltage unbalance, distorted voltage and current and variable power factors in each phase can be observed. An efficient algorithm to mitigate unbalanced and distorted load and source voltage and current in solar photo voltaic (PV) inverter for isolated load system was considered. This solar PV system can be applicable to remote located industrial loads like heating, welding and small arc furnace type distorted loads and also for unbalanced loads. The PV inverter is designed such that it will maintain nearly constant voltage magnitude and can mitigate harmonics in voltage and current near the load terminals. A MATLAB/ SIMULINK based solar PV inverter was simulated and results are compared with standard AC three phase grid connected system. The proposed shows that the inverter is having very less voltage and current harmonic content and can maintain nearly constant voltage profile for highly unbalanced system.